Cover Feature: Tunable Thiolate Coordination Networks on Metal Surfaces (ChemNanoMat 10/2020). Issue 10 (28th September 2020) - Meng, Xiangzhi; Kolodzeiski, Elena; Huang, Xing; Timmer, Alexander; Schulze Lammers, Bertram; Gao, Hong‐Ying; Mönig, Harry; Liu, Lacheng; Xu, Wei; Amirjalayer, Saeed; Zhu, Daoben; Fuchs, Harald
Abstract : Tunable thiolate coordination networks were prepared on metal surfaces using benzenehexathiol (BHT) under ultrahigh vacuum conditions. The two‐dimensional (2D) coordination networks achieved via thermal annealing give diverse structures on different surfaces. The structures of the networks on the copper surface could be well tuned by adjusting the thermal condition of the surface. Understanding the significant role of the metal surfaces will bring more information in the controllable synthesis of 2D coordination materials. More information can be found in the Communication by Wei Xu, Saeed Amirjalayer, Daoben Zhu, Harald Fuchs et al.